Medulloepithelioma with peculiar clinical presentation, stem cell phenotype and aberrant DNA-methylation profile - Ozolek, John A.; Cohen, Debra E; Kool, Marcel; Pfister, Stefan; Korshunov, Andrey; Bukowinski, Andrew J; Davis, Amy W (CNS Oncology, 2015)
SUMMARY We present a 21-year-old male with a neck mass diagnosed as medulloepithelioma. Despite aggressive chemo- and radio-therapy, the tumor metastasized and proved fatal after seventeen months. The tumor demonstrated robust immunohistochemical expression of multiple markers of embryonic/neural stem cells and embryogenesis from the paraffin embedded tissue. The tumor, expressing LIN28A but negative for the 19q13.42 amplicon, also lacked the characteristic methylation profile for medulloepithelioma and other tumors with similar morphology. The expression of embryonic markers may explain its unresponsiveness to therapy and poor prognosis. Therapies targeted at embryonic cell phenotypes may hold the key for successfully treating cancers with embryonal phenotypes or tumors harboring cells with embryonal phenotypes.
Gesehen am 26.06.2020